Glucose Toxic Effects on Granulation Tissue Productive Cells: The Diabetics' Impaired Healing. (26th December 2012) - Berlanga-Acosta, Jorge; Schultz, Gregory S.; López-Mola, Ernesto; Guillen-Nieto, Gerardo; García-Siverio, Marianela; Herrera-Martínez, Luis
Abstract : Type 2 diabetes mellitus is a metabolic noncommunicable disease with an expanding pandemic magnitude. Diabetes predisposes to lower extremities ulceration and impairs the healing process leading to wound chronification. Diabetes also dismantles innate immunity favoring wound infection. Amputation is therefore acknowledged as one of the disease's complications. Hyperglycemia is the proximal detonator of systemic and local toxic effectors including proinflammation, acute-phase proteins elevation, and spillover of reactive oxygen and nitrogen species. Insulin axis deficiency weakens wounds' anabolism and predisposes to inflammation. The systemic accumulation of advanced glycation end-products irreversibly impairs the entire physiology from cells-to-organs. These factors in concert hamper fibroblasts and endothelial cells proliferation, migration, homing, secretion, and organization of a productive granulation tissue. Diabetic wound bed may turn chronically inflammed, procatabolic, and an additional source of circulating pro-inflammatory cytokines, establishing a self-perpetuating loop. Diabetic fibroblasts and endothelial cells may bear mitochondrial damages becoming prone to apoptosis, which impairs granulation tissue cellularity and perfusion. Endothelial progenitor cells recruitment and tubulogenesis are also impaired. Failure of wound reepithelialization remains a clinical challenge while it appears to be biologically multifactorial. Ulcer prevention by primary care surveillance, education, and attention programs is of outmost importance to reduce worldwide amputation figures.